Recent Advances in Autism Spectrum Disorders - Volume I 2013
DOI: 10.5772/54784
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Approach in Autism: Management and Treatment

Abstract: By definition, in autism the social deficits are characterized by lack of interest in spontaneously sharing feelings, different levels of communication deficits, difficulties in imaginative plays, restrictive repertoire of interests, non-functional routine fixations, as well as stereotypies and other motor alterations, such as flapping with hands, circular movements and others (Nikolov, Jonker, and Scahill 2006; Gadia, Tuchman, and Rotta 2004). While the criteria of the DSM-V (Diagnostic and Statistical Manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…This finding replicates the results of a recent study that identified hyperactivity and irritability to be associated with children's CAM use [15]. Externalizing behaviours in ASD are often treated with psychotropic medication [44], specifically methylphenidate (Ritalin) [45][46][47] and Dexamphetamine (Dexedrine) [48,49]. It is possible that the link between psychotropic medication and CAM use observed in the current study is a reflection of parents seeking multiple medications to treat the same behaviours in a bid to find an effective treatment for their child with ASD-a life-long condition.…”
Section: Discussionsupporting
confidence: 88%
“…This finding replicates the results of a recent study that identified hyperactivity and irritability to be associated with children's CAM use [15]. Externalizing behaviours in ASD are often treated with psychotropic medication [44], specifically methylphenidate (Ritalin) [45][46][47] and Dexamphetamine (Dexedrine) [48,49]. It is possible that the link between psychotropic medication and CAM use observed in the current study is a reflection of parents seeking multiple medications to treat the same behaviours in a bid to find an effective treatment for their child with ASD-a life-long condition.…”
Section: Discussionsupporting
confidence: 88%
“…There are two complementary issues in the clinical approach for autism. The first is the general management, including diagnosis and evaluation of the intensity level of eventual core behavioral symptoms ( 9 ). The second considers treatment options, such as psychopharmacotherapy and different types of non-medical treatments.…”
Section: Clinical Approach and Molecular Phenotypesmentioning
confidence: 99%
“…Risperidone was approved in 2006 by the FDA at a typical dose of 1–3 mg/day. In 2009, aripiprazole was ratified by the FDA at a typical dose of up to 15 mg/day ( Riesgo, R., Gottfried, C., & Becker, 2013 ; Lord et al, 2018 ; DeVane et al, 2019 ; Hongkaew et al, 2021b ; Biswas et al, 2022b ).…”
Section: Therapeutic Guidelines For Asdmentioning
confidence: 99%